Hopf Bifurcation of a Delayed Ecoepidemic Model with Ratio-Dependent Transmission Rate - Wanjun Xia; Soumen Kundu; Sarit Maitra (Journal of Function Spaces)
A delayed ecoepidemic model with ratio-dependent transmission rate has been proposed in this paper. Effects of the time delay due to the gestation of the predator are the main focus of our work. Sufficient conditions for local stability and existence of a Hopf bifurcation of the model are derived by regarding the time delay as the bifurcation parameter. Furthermore, properties of the Hopf bifurcation are investigated by using the normal form theory and the center manifold theorem. Finally, numerical simulations are carried out in order to validate our obtained theoretical results.